Assessment, teacher education and the emergence of professional expertise. (10th April 2017) - Ellis, Sue; Smith, Vivienne
Abstract: This paper describes a new assessment tool that situates school literacy as a specific cognitive, cultural, social and emotional. It reports evidence of the extent to which this tool seems to have helped student teachers to broker and balance different kinds of data and knowledge flows. The study shows that the tool was helpful in encouraging student teachers to deepen their understanding of individual knowledge domains and to orchestrate across them to determine pathways to impact, learning priorities and actions. Its theoretical contribution is to suggest that there are benefits in recasting assessment and the professional knowledge that underpins it as a problem of how to align evidence from different theoretical and practice knowledge communities. Its contribution to the policy debate is to suggest that this could create a climate for more productive conversations between researchers, policy makers and practitioner communities.